Implementing WebSphere Business Integration Express for Item Synchronization - Gavin, Lee (IBM, 2004)
Today's suppliers, consumer packaged goods companies, manufacturers, and wholesalers face many challenges. Each year, 20 000 new food and non-food Universal Product Code (UPC) items are created and it typically takes 10 to 30 days to get these new items and price changes to market. Data elements that describe these individual items may change up to four times per year. Furthermore, nearly three out of five orders placed need to be revisited and reworked before completion. To meet these escalating data demands on suppliers, UCCnet has implemented multi-industry standards for product identification and related electronic communications. A subsidiary of the Uniform Code Council Inc., UCCnet is a neutral industry organization that implements these standards by requiring its community of trading partners to provide standardized item data in particular formats to its registry. This IBM Redbooks publication covers IBM WebSphere Business Integration Express for Item Synchronization, which is designed for mid-market suppliers pursuing supply chain integration through the UCCnet GLOBALregistry. Please note that the additional material referenced in the text is not available from IBM.
Includes bibliographical references and index. - Print version record
Keywords: WebSphere; Inventory control -- Computer programs; Web servers -- Computer programs; Software configuration management; Gestion des stocks; Logiciels; Serveurs Web; Logiciels; Logiciels; Gestion de configurations; Inventory control; Computer programs; Web servers; Computer programs; Software